Electrospinning, preparation and photoluminescence properties of CoNb2O6:Dy3+ incorporated polyamide 6 composite fibers - EKMEKÇİ, METE KAAN (ELSEVIER, 2017)
3 mol% Dy3+ doped cobalt niobate (CoNb2O6) compound has been synthesized by molten salt method using Li2SO4/Na2SO4 salt mixture as a flux at a relatively low temperature as compared to solid state reaction. X-ray diffraction patterns of 3 mol% Dy3+ doped CoNb2O6 compound indicated orthorhombic columbite single phase. SEM analysis revealed that Dy3+ doped CoNb2O6 has a submicron particle size. The photoluminescence of CoNb2O6: Dy3+ phosphor has exhibited in a dominant yellow emission at 579 nm with an excitation wavelength of 366 nm. The synthesized submicron phosphor particles were successfully incorporated into Polyamide 6 fibers by utilizing electrospinning technique. The average fiber diameter obtained through the process ranged between 192 +/- 62 nm and 387 +/- 341 nm. Mechanical characteristics of the produced nanofibrous webs were strongly influenced by the fiber morphologies and size (diameter) distribution rather than the phosphor particles incorporated into the fibers and/or located on the web. The photoluminescence of composite fiber material increased with the increasing phosphor content. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Electrospinning; Composite fiber; Columbite CoNb2O6; Optical properties; XRD; SEM-EDS; MOLTEN-SALT SYNTHESIS; LUMINESCENCE; DY3+; EU3+